2016
DOI: 10.3847/0067-0049/222/2/19
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Survey of G and K Dwarfs in the Hipparcos Catalog. I. Comparison Between the Hipparcos and Photometric Parallaxes

Abstract: The tension between the Hipparcos parallax of the Pleiades and other independent distance estimates continues even after the new reduction of the Hipparcos astrometric data and the development of a new geometric distance measurement for the cluster. A short Pleiades distance from the Hipparcos parallax predicts a number of stars in the solar neighborhood that are sub-luminous at a given photospheric abundance. We test this hypothesis using the spectroscopic abundances for a subset of stars in the Hipparcos cat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…This comparison between the Hipparcos field stars implies that the reference parallax of the field twins are accurate. It further confirms the analysis of Kim et al (2016) who found that Hipparcos parallax to FGK field stars similar to Pleiades member stars are in good agreement with stellar models. Figure 3 shows the parallax of individual Pleiades stars, in which our results are compared with the literature (Makarov 2002;Soderblom et al 2005;van Leeuwen 2007).…”
Section: Resultssupporting
confidence: 89%
“…This comparison between the Hipparcos field stars implies that the reference parallax of the field twins are accurate. It further confirms the analysis of Kim et al (2016) who found that Hipparcos parallax to FGK field stars similar to Pleiades member stars are in good agreement with stellar models. Figure 3 shows the parallax of individual Pleiades stars, in which our results are compared with the literature (Makarov 2002;Soderblom et al 2005;van Leeuwen 2007).…”
Section: Resultssupporting
confidence: 89%
“…SSPP has successfully passed a series of tests for validating the accuracy of spectroscopic parameters using high-resolution spectra and Galactic cluster data (Allende Prieto et al 2008;Lee et al 2008a,b). Recently, Kim et al (2016) applied the modified spectral matching technique, like the one used in this work, to high-S/N (> 100) spectra of bright G-and K-type dwarfs in the solar neighborhood, after downgrading spectra to R ∼ 10, 000, to validate stellar parameters against those based on equivalent-width analysis using MOOG (Sneden 1973).…”
Section: Stellar Parameters and Cluster Membershipmentioning
confidence: 99%
“…To briefly summarize the spectral matching technique adopted in this study (see also Kim et al 2016), we employed the χ 2 minimization routine MPFIT (Markwardt 2009) to search the grid of synthetic spectra for the best-fitting set of T eff , log g, and [Fe/H] for an observed spectrum. Radial velocity (v r ) measurements were followed through cross-correlation with a synthetic spectrum.…”
Section: [Fe/h] T Eff Log G and V Rmentioning
confidence: 99%
“…To mitigate the effects that small differences in exposure time across our survey can have, we use count rates as a measure of intensity. We define the hardness ratio as the ratio between the count rate in the 2.5-8 keV minus that in the 0.3-2.5 keV band to the count rate in the full 0.3-8 keV energy band (after Kim et al 2004). We derived the hardness using XSPEC version 12.7 (Arnaud 1996) by determining the count rates in the soft and hard band taking the response and ancillary response file for each of the sources.…”
Section: Source Detectionmentioning
confidence: 99%